Book review: Thomas Piketty, Capitalul în secolul XXI - UŢĂ, Cristian (Annals of Spiru Haret University. Economic Series, 2015)
Litera Publishing, Bucharest, 2015 Translation from French by Irina Brateş and Lucia Popovici